0D/3D ZnIn2S4/Ag6Si2O7 nanocomposite with direct Z-scheme heterojunction for efficient photocatalytic H2 evolution under visible light. (10th August 2021) - Kong, Dezhi; Ruan, Xinxing; Geng, Jiankun; Zhao, Yihan; Zhang, Dafeng; Pu, Xipeng; Yao, Shujuan; Su, Changhua
Abstract: Constructing heterojunction structure is a feasible way to realize an efficient and durable photocatalysts. Herein, a novel Z-scheme zero/three dimensional (0D/3D) ZnIn2 S4 /Ag6 Si2 O7 (ZIS/ASO) composite was rationally designed, synthesized and analyzed. ZIS/ASO composite possesses a layer structure for increasing light response, a special 0D/3D structure for reducing the photo-induce carriers migration path, and numerous active sites for absorbing H2 O and producing H2 . This composite retains the high oxidation and reduction ability by facilitating separation and migration as well as limiting recombination of photo-induced carriers via the intimate interface between ZIS and ASO. Undoubtedly, the synthesized ZIS/ASO photocatalyst achieved a high photocatalytic H2 activity, and the optimum sample shows a satisfactory H2 evolution rate of 590.56 μmol g −1  h −1, distinctly better than that of pure ZIS. More importantly, this composite exhibits high stability and recyclability and is expected to be applied in practical application. Based on the H2 evolution experimental results and electrochemical tests, the Z-scheme heterostructure construction of the composite was confirmed. This work expects to inspire a unique protocol for synthesizing Z-scheme photocatalysts for water splitting under visible light irradiation. Highlights: ZnIn2 S4 /Ag6 Si2 O7 composites were synthesized by an ultrasound-calcination method. The hierarchical structure could distinctly improve the charge-carriers transfer. The composites showed superior photocatalytic H2 evolution activity and recyclability. Z-scheme photocatalytic mechanism was proposed.